Development of investigative skills in graduates from the Graduate School. César Vallejo University (Revista Electrónica Calidad en la Educación Superior, 2020)
The skills of an investigator are basic conditions; whose main activity is to seek new knowledge in the scientific field; The main objective of this research was to diagnose the level of development of investigative skills of the teachers. The research design was descriptive evaluative and the sample of 65 subjects was administered a questionnaire with responses on a Likert scale. According to the observed abilities, the results show the following, in the empirical analytical knowledge 13.8% demonstrate a very high development; medium 30.8% and low 33.8%. In the hermeneutical historical knowledge 1.5% reached a very high development, average 20% and under 35.4% and; finally, in critical knowledge 4.6% show a very high development, medium 30.8%, and low 43.1%. It is concluded that there is no relevant percentage difference in the development of investigative skills according to the type of knowledge.
Keywords: Skill; development of investigative; empirical; analytical; hermeneutical; critical ability